Edukasi Higiene dan Sanitasi Makanan melalui Media Poster H.I.G.I.E.N.I.S pada Pekerja Pabrik Kerupuk di Kecamatan Cibeureum Kota Tasikmalaya - Analisa Salsabila; Mala Nuraeni; Santi Shopiah; Alma Aulia Shapira; Ersya Sri Oktaviani; Nidya Elpara Dika; Anita Rahmawati; Kamelia Pemiliani (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Hygiene and food sanitation are crucial practices for any business that produces food products. The implementation of hygiene and sanitation in food factories is essential, as it significantly impacts the health of consumers, workers, and the overall development of the company. Consumers tend to prefer safe, clean, and healthy products. Observations conducted at a cracker factory located in Setiajaya Village, Cibeureum District, Tasikmalaya City revealed that the application of food hygiene and sanitation was not fully implemented. Consequently, a series of educational activities were organized to emphasize the importance of hygiene and sanitation in the cracker production process. The aim of these activities was to enhance workers' awareness and compliance with food hygiene and sanitation practices. Direct engagement with workers was employed through educational posters based on the H.I.G.I.E.N.I.S. approach. The educational initiative was met with enthusiasm from the workers, which is expected to improve their understanding of hygiene and sanitation practices in the cracker factory. This initiative highlights the necessity for ongoing education to maintain food safety standards and protect consumer health.